Chronic Disease Prevalence Among Mothers Delivering in the United States, 2004-2013 [38N]. (May 2017) - Admon, Lindsay; Winkelman, Tyler; Moniz, Michelle; Davis, Matthew; Heisler, Michele; Dalton, Vanessa
Abstract : INTRODUCTION: Reasons for nationwide increases in delivery-associated maternal morbidity and mortality are poorly understood. Pre-existing chronic disease increases the risk of obstetric complications, and there is a need to understand trends in chronic disease burden among the childbearing population. METHODS: We conducted a serial cross-sectional analysis of the National Inpatient Sample between 2004 and 2013. We used multivariable logistic regression, adjusted for age, income, and insurance status, to examine trends in chronic disease among delivery hospitalizations. Chronic disease was measured with ICD-9CM codes for 8 common conditions known to impact obstetric outcomes. RESULTS: Our sample was comprised of 8, 307, 761 delivery hospitalizations between 2004-2013. The mean age of delivering mothers was 27.7. The most prevalent conditions were respiratory disease, hypertension, and drug abuse (3.0, 1.9 and 1.4 per 100 delivery hospitalizations, respectively). In adjusted analyses, records in 2012/2013 were more likely than those in 2004/2005 to include diagnoses of diabetes, hypertension, respiratory disease, liver disease, kidney disease, and drug use (all P less than 0.001) and less likely to have diagnoses of heart disease (P less than 0.001) or HIV (P equal to 0.02). Delivery hospitalizations in 2012/2013 were also more likely than those in 2004/2005 to be complicated by at least one or at least two chronic conditions (both P less than 0.001). CONCLUSION: Chronic disease burden increased significantly among delivering mothers between 2004/2005 and 2012/2013. Higher proportions of women with chronic conditions and higher numbers of chronic conditions per patient may contribute to increases in delivery-associated morbidity and mortality.